The ideology of education : the commonwealth, the market, and America's schools - Smith, Kevin B., 1963- (State University of New York Press, 2003)
"Advocates of market-based education reforms (including such policies as choice, charters, vouchers, and outright privatization) argue that they represent ready solutions to clearly defined problems. Critics of market models, on the other hand, argue that these reforms misperceive the purposes of public education and threaten its democratic ethos. This book explores both the promises and pitfalls of market forces - their potential to improve the quality of public education and their compatibility with its republican justifications. Smith argues that although market models of education are not without utilitarian merit, their potential to alter the social-democratic purposes of education is seriously underestimated. He supports this claim with a series of sophisticated analyses of the key assumptions underlying these models, and by examining the normative elements of theory and methodology that can - and often do - skew empirical policy analysis toward market preferences. He concludes that market reforms are not just a ready means to effectively address the problems of public schooling but rather represent a clear attempt to ideologically redefine its ends."--Jacket